Conformational landscape and metal-molecule interaction of diverse molecular systems: Insights from ab initio electronic structure calculations. - Bhadoria, Poonam (IIT(BHU) Varanasi, 2023)
Abstract is available in the attachment.
Keywords: Chemistry